DIAGNOSTIC VALIDITY ANALYSIS OF NS1-BASED RAPID TEST COMPARED WITH RT-PCR FOR DENGUE DETECTION IN BATAM - Dewi Inderiati; Yuli Yanti; Anita Sofia; Citra Amaniah Anhar (Meditory : The Journal of Medical Laboratory, 2025)
Background: Dengue remains a significant health problem in Indonesia, including Batam. Because its symptoms resemble other infections, early laboratory testing is crucial. The non-structural protein one rapid diagnostic test (NS1 RDT) is widely used, but its accuracy depends on the day of illness, immune status, and viral serotype.Objective: To evaluate the diagnostic validity of NS1 RDT compared to RT-PCR, assessing the level of agreement between the two methods, and analysing the influence of clinical phase and serotype on the results of the examination.Methods: A retrospective analytic study used secondary data from 309 suspected dengue cases tested by NS1 RDT at primary care and confirmed by RT-PCR with serotyping at Batam Public Health Laboratory (2022–2024). Diagnostic performance was calculated from 2×2 tables; concordance was analysed with McNemar's test and Cohen's kappa.Results: The NS1 RDT showed 75.8% sensitivity, 81.2% specificity, 62.7% positive predictive value, 88.9% negative predictive value, and 79.6% overall accuracy, with moderate agreement with RT-PCR (κ = 0.54). NS1 positivity peaked on illness days 1–3 and varied by serotype, with the highest for DENV-3.Conclusions: The NS1 RDT showed good diagnostic validity with moderate agreement and sensitivity and high specificity in early dengue disease screening compared to RT-PCR, so the diagnostic performance of the NS1 RDT can be used in local epidemiological testing in Batam.